Shadow of doubt : a thriller [large type] - Thor, Brad (Thor, Brad. Scot Harvath, 2024)
"A mysterious cargo plane, flanked by a squadron of Russia's most lethal fighters, has just taken off from a remote airbase. Although closely monitored by the United States, no one inside the Pentagon has any idea where it's going or what it's carrying. A high-level Russian defector, a walking vault of secrets that could shatter the West, seeks asylum in Norway. Across the continent, in the heart of Paris, a lone French agent stumbles upon a conspiracy so explosive it could ignite a global firestorm. As alarm bells ring in Washington, the CIA's most lethal weapon, Scot Harvath, is forced to choose between his conscience and his country"--